Bird Species in Rojolelo Forest Park (TAHURA) Central Bengkulu, Bengkulu - Eki Susanto; Evelyne Riandini; Riki Rahmansyah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Rojolelo Forest Park (TAHURA) is a green open space in Central Bengkulu Regency. The research aimed to determine the species, diversity, and conservation status of birds in the Rojolelo Forest Park (TAHURA) Central Bengkulu Regency. The research was conducted February-April 2022 in three locations such as Shrubs, Irrigation dan TAHURA Office. The sample used point counts method. The Research showed 33 bird species from 21 families and 115 individuals, the diversity index (H’) = 3, 01. The family most commonly was founded Nectariniidae (4 species). Five bird species were protected such as Meiglyptes tukki (Buff-necked woodpecker), Eurylaimus ochromalus (Black and yellow broadbill), Ictinaetus malayensis (Black Eagle), Spilornis cheela (Crested serpent Eagle), and Pitta sordida (Hooded Pitta).